Effects of habitat loss on migratory shorebird community structure at stopover sites: A case study in the Yellow River Delta, China - Duan, Houlang; Yu, Xiubo; Shan, Kai; Zhang, Chenghui; Liu, Haifang (Frontiers in Marine Science, 2022)
Coastal wetlands in China provide important stopover sites for migratory shorebird species. The loss of natural wetlands caused by land reclamation over the past few decades poses a major threat to shorebird populations. Although habitat loss at key stopover sites has been shown to lead to reductions in shorebird populations, the effects of habitat loss at specific stopover sites on shorebird populations remain unclear. Here, we used shorebird diversity indices and landscape metrics to elucidate the long-term (19952020) effects of habitat change on shorebird community structure in the Yellow River Delta, which is an important stopover site for shorebirds along the Yellow Sea coast. The results showed that the habitat area, largest patch index, mean patch area, and the aggregation index decreased over 25 years. By contrast, the number of patches and patch density increased over the same period. The richness, Shannon-Wiener index, Pielou index, and Simpson index of the shorebird community increased from 1995 to 2020, while abundance of shorebird declined by 90.14%. Declines in the abundance of species were more pronounced in larger-bodied ones than in smaller-bodied species (T=1.156, df=42, p=0.02). On the other hand, there were no significant differences in the decline in the abundance of threatened species and non-threatened species (T=-0.483, df=42, p=0.632) and coastal specialist species and generalist/inland specialist species (T=-1.197, df=42, p=0.239). The decrease in mean patch area significantly contributed to the reduction in abundance of shorebirds (N=6, p=0.01), and its effects were more pronounced on larger-bodied ones than on smaller-bodied species (T=-2.113, df=42, p=0.04). These results suggest that habitat loss in the Yellow River Delta has contributed to declines in shorebird populations and that larger-bodied ones are more sensitive to habitat change than smaller-bodied species. Existing wetlands are in urgent need of conservation, and further land reclamation in this region should be avoided. In addition, the development of conservation plans for coastal wetlands requires consideration of variation in the responses of different functional groups to habitat change.